(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article is about foreign language teaching methodology and foreign language teaching method. The use of various methods and tools to interest students and young people in educational classes, the most important of which is to improve professional skills in foreign language teaching and the use of modern methods during teaching. together with the types of studies in the methodology of foreign language teaching.